Study of multispectral polarization imaging in sea fog environment - Fu, Qiang; Yang, Wei; Si, Linlin; Zhang, Meng; Zhang, Yue; Luo, Kaiming; Zhan, Juntong; Zhang, Su (Frontiers in Physics, 2023)
Marine exploration has become a popular field of concern and research all over the world. The impact of sea fog on ocean exploration is very great, and how to carry out accurate identification of targets in the sea fog environment is a problem we urgently need to solve. In this paper, we simulated and analyzed the particle distribution characteristics of the sea fog layer by using the principle of Mie scattering, designed a spectral polarization imaging system by using Liquid Crystal Variable Retarder (LCVR)and Liquid Crystal Tunable Filter(LCTF) according to the principle of spectral spectroscopy and polarization imaging, conducted calibration experiments on liquid crystal tunable filter, and carried out experiments on visibility, wavelength and imaging distance that affect the experimental results of polarization imaging of sea fog environment. The experimental results show that the polarization decreases with the increase of imaging distance; in the typical visibility (5km for light fog, 0.5km for medium fog and 0.05km for dense fog), the higher the visibility, the higher the polarization; for the typical wavelengths of visible light (450nm, 530nm and 670nm), the polarization increase with the increase of wavelength.